Incommensurability, types of phenomena and relevant incompatibility (part II) - Céspedes, Esteban (Cinta de Moebio. Revista de Epistemología de Ciencias Sociales, 2019)
This is the second part of a three-part paper. In part I, some of the main issues regarding theoretical incommensurability and meaning invariance were considered, introducing the notion of a phenomenon type. Phenomenon types can be treated as subject matters in order to tackle the mentioned issues. Here, I show how a subject matter can be conceived as a common ground of two conflicting theories. However, crucial problems about realism and scientific progress remain. These are introduced in this part of the paper and will be tackled in part III.